S16 Simvastatin improves neutrophil migration in elderly patients with septic pneumonia and reduces 6-month mortality and re-admissions: results of the snoopi trial. (15th November 2016) - Patel, J; Greenwood, H; Lugg, S; Howells, P; Gao, F; Sapey, E; Thickett, D
Abstract : Introduction and objectives: Community acquired pneumonia is a leading infectious cause of death in the elderly and the commonest source of sepsis. Neutrophil functions decline with age, and deteriorate further in sepsis. 1 Restoring neutrophil function may improve sepsis outcomes. Recent in-vitro and in-vivo studies suggest simvastatin improves aspects of neutrophil function. 2 Adjuvant statin therapy in severely critically ill patients has failed to improve outcomes and may be associated with increased morbidity, 4, 5 however our ASEPSIS study suggested that early intervention with statins may reduce the progression of sepsis in a ward-based cohort of milder sepsis patients. 6 In light of this, we investigated whether oral treatment with simvastatin improved neutrophil function and clinical outcomes in elderly patients with septic pneumonia. Methods: 'SNOOPI' was a phase-4, randomised controlled trial comparing 7-days of 80mg simvastatin with placebo in patients aged 55 years or over admitted to hospital with septic pneumonia. 3 The primary outcome was changes in neutrophil extracellular trap (NETs) formation by day3/4 compared with baseline. Secondary outcomes included neutrophil migration, safety and tolerability, length of stay, readmissions and mortality. Results: 61 patients were recruited acute admissions unit at the Queen Elizabeth Hospital Birmingham between 2013 and 2015, with 31 patients randomised to simvastatin and 30 to placebo. Groups were well matched for baseline characteristics, pneumonia and sepsis severity, co-morbidities and biochemical and haematological parameters. There was no significant difference in the primary end-point of change in NETS at day3/4. Directional neutrophil migration (chemotaxis) was significantly improved in patients who received simvastatin at day 3/4 (0.35 ± 0.16 μm/min vs. −0.15 ± 0.17 μm/min; p = 0.033). Simvastatin was well tolerated with no SUSARS, even with the co-prescription of macrolides. At 6-months, patients in the simvastatin group were less likely to have been admitted to hospital or died compared to those in the placebo group (OR: 0.44; 95% CI: 0.21–0.91; p = 0.02) (Figure 1 ). Conclusions: The current study suggests that early intervention with statins in septic pneumonia patients may improve patient outcomes. We propose that one of the mechanistic drivers may be the restoration of sepsis-associated dysregulated neutrophil function. Further larger studies are warranted to confirm whether early intervention with statins in patients with sepsis confer an overall survival benefit. References: Alves-Filho JC, Spiller F, Cunha FQ. Neutrophil paralysis in sepsis. Shock 2010;34 (Suppl 1):15–21. Sapey E, Greenwood H, Walton G, et al . Phosphoinositide 3-kinase inhibition restores neutrophil accuracy in the elderly: toward targeted treatments for immunosenescence. Blood 2014;123 (2):239–248. Greenwood H, Patel J, Mahida R, et al . Simvastatin to modify neutrophil function in older patients with septic pneumonia (SNOOPI): study protocol for a randomised placebo-controlled trial. Trials 2014;15 :332. McAuley DF, Laffey JG, O'Kane CM, et al . Simvastatin in the acute respiratory distress syndrome. N Engl J Med 2014;371 :1695–1703. The National Heart L, Blood Institute ACTN. Rosuvastatin for sepsis-associated acute respiratory distress syndrome. N Engl J Med 2014;370 :2191–2200. Patel JM, Snaith C, Thickett DR, et al . Randomised double-blind placebo-controlled trial of 40 mg/day of atorvastatin in reducing the severity of sepsis in ward patients (ASEPSIS Trial). Critical Care 2012;16 (6):R231.